Serum mitochondrial-encoded NADH dehydrogenase 6 and Annexin A1 as novel biomarkers for mortality prediction in critically ill patients with sepsis - Zhou, Fan; Chen, Meiling; Liu, Yilin; Xia, Xianzhu (Frontiers in Immunology, 2024)
ObjectivesFormyl peptide receptor 1 (FPR1) is a member of G protein-coupled receptor (GPCR) family that detects potentially danger signals characterized by the appearance of N-formylated peptides which originate from either bacteria or host mitochondria during organ injury, including sepsis. Mitochondrial-encoded NADH dehydrogenase 6 (MT-ND6) and Annexin A1 (ANXA1), as mitochondrial damage-associated molecular patterns (mtDAMPs) agonist and endogenous agonist of FPR1 respectively, interact with FPR1 regulating polymorphonuclear leukocytes (PMNs) function and inflammatory response during sepsis. However, there is no direct evidence of MT-ND6 or ANXA1 in the circulation of patients with sepsis and their potential role in clinical significance, including diagnosis and mortality prediction during sepsis.MethodsA prospective cohort study was conducted in ICU within a large academic hospital. We measured serum MT-ND6 or ANXA1 in a cohort of patients with sepsis in ICU (n=180) and patients with non-sepsis in ICU (n=60) by Enzyme-linked immunosorbent assays (ELISA). The ROC curve and Kaplan Meier analysis was used to evaluate the diagnostic and prognostic ability of two biomarkers for patients with sepsis.ResultsThe concentration of MT-ND6 and ANXA1 were significantly elevated in the patients with sepsis, and the diagnostic values of MT-ND6 (0.789) for sepsis patients was second only to SOFA scores (AUC = 0.870). Higher serum concentrations of MT-ND6 (>1.41 ng/ml) and lower concentrations of ANXA1 (< 8.09 ng/mL) were closely related to the higher mortality in patients with sepsis, with the predictive values were 0.705 and 0.694, respectively. When patients with sepsis classified based on four pro-inflammation and two anti-inflammation cytokines, it was shown that combination of MT-ND6 and ANXA1 obviously improved the predictive values in the septic patients with mixed hyperinflammation or immunosuppression phenotypes.ConclusionOur findings provide valuable models testing patient risk prediction and strengthen the evidence for agonists of FPR1, MT-ND6 and ANXA1, as novel biomarker for patient selection for novel therapeutic agents to target mtDAMPs and regulator of GPCRs in sepsis.